Public administration in contested societies - O'Connor, Karl.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
Why are some conflicts managed better than others? Social scientists have used various disciplinary lenses to answer this question but until now, public administration has not been used to understand how conflict is managed. This book explores the everyday management of conflict in two cases of power-sharing from the view of elite level bureaucrats.
Keywords: Science; Science; Science, general